Indagine conoscitiva sull’esposizione personale dei lavoratori a silice libera cristallina in edilizia / A survey on workers’ individual exposure to crystalline silica in the building industry” - Miscetti, G.; Bodo, P.; Garofani et al., P. (La Medicina del Lavoro, 2011)
«A survey on workers’ individual exposure to crystalline silica in the building industry». Background: The widespread presence of silica in nature and the variety of materials containing it cause crystalline silica exposure of workers in various industrial activities. Moreover crystalline silica is classified as carcinogenic to humans (Group 1) by IARC, in relation to its possible lung carcinogenicity. Objectives and methods: The purpose of this paper was to assess respirable particles and crystalline silica exposure of workers  in a number of some building sites located in the area of a Local Health Unit in the Umbria region. The study examined differences  in four types of building sites: “construction of new buildings”, “renovation of old buildings”, “road construction” and “transport of aggregates by loaders in crushing plants”. According to the strategy suggested by European Standard EN 689/1997, personal air samples were collected during work in jobs characterized by elevated amounts of widespread dust. Results and conclusions: Analysis of data showed that levels of exposure to crystalline silica were lower than the limits recommended by ACGIH/2010 in almost all samples except one. The percentages of crystalline silica in respirable particles were in the range 0.4%-21%. Crystalline silica exposure levels  were different in the various jobs and comparison between the mean values of exposure levels in each one showed statistically significant differences (p